The semantic and structural properties of modal markers in old Lithuanian writings (the 16th century) - Jasionytė-Mikučionienė, Erika (Lietuvių kalba, 2016)
The present study examines the expression of modality in the 16th century texts of Old Lithuanian, namely in Jonas Bretkūnas’ Postilė (1591) and Mikalojus Daukša’s Postilė (1599). The aim of the study is to compile the inventory of the modal markers and to give a description of semantic as well as structural features of the modals in the selected old Lithuanian writings. The results show that although the range of modal markers in the 16th century is wide and varied, the expressions of non-epistemic modality are more diverse than the expressions of epistemic modality. The former are expressed by the verbs reikėti ‘need to’, turėti ‘have to’, pareiti(s(i)) ‘have to’, gauti ‘get’, derėti ‘ought to’, the constructions būti privalu ‘be obligatory’ and būti valnu ‘be allowed’, while the latter are expressed by the adverb veikiai (veikiaus) ‘soon’ and the verbal form regis ‘it seems/seemingly’, etc. The greater variety of non-epistemic markers could have been determined by two factors. One of the factors may be that epistemic meanings were not as developed as non-epistemic meanings in the 16th century (it is compatible with the universal development of non-epistemic meaning into epistemic meaning in other languages). The other factor may be connected with the type of texts under study. Deontic meaning prevails in the 16th century texts due to their religious character. They instruct the reader how to follow God‘s commandments and thus live according to God‘s will.
Keywords: modality; modal system; modal markers; epistemic modality; non-epistemic modality; Old Lithuanian writings